Efeitos do treinamento muscular inspiratório de alta intensidade associado ao exercício aeróbico e resistido pós revascularização do miocárdio - Santos, Tamires Daros dos (2017)
There is growing debate around the inclusion of inspiratory muscle training (IMT) to cardiac rehabilitation (CR) programs. Inspiratory muscle training has been included specifically for patients who underwent coronary artery bypass grafting (CABG). This was done not only in Phase I of CR, but also in phase II, since effects on pulmonary function and reduction in functional capacity (FC) are still present in late stages. This study had the aim of investigating the effects of the addition of high-intensity IMT to the aerobic and resistance (combined training - CT) training of patients after CABG (Phase II). A randomized clinical trial was conducted with 24 post-CABG patients randomly divided into two groups: SIMTG+CT (n=12), which performed sham IMT in association with CT, and IMTG+CT (n=12), who underwent high-intensity IMT in association with CT, for 12 weeks, twice a week. The following parameters were assessed before and after intervention: maximal FC, through cardiopulmonary exercise test (VO2 peak); submaximal FC, through the six-minute walk test (6MWT); quality of life (QoL), through the Minnesota Living with Heart Failure Questionnaire (MLHFQ); respiratory muscle strength (MIP and MEP) through manovacuometry; pulmonary function (FVC and FEV1) through spirometry; inspiratory muscle resistance (SMIP and Tlim) through manovacuometer and POWERbreathe®. Considering laboratory markers, assessment of oxidative profile was performed with advanced oxidation protein products (AOPPs); antioxidant profile through the ferric reducing method (FRAP); endothelial function through nitrite/nitrate (NOx) and inflammatory profile through high-sensitivity C-reactive protein (hsCRP). There was significant increase in VO2 peak both in SIMTG+CT (p<0.0001) and in IMTG+CT (p<0.0001). When comparing groups, a significant increase was observed in IMTG+CT (p=0.0412). Distance walked on the 6MWT significantly increased in SIMTG+CT (p<0.0001) and in IMTG+CT (p<0.0001). However, there was a significant increase in IMTG+CT in comparison to SIMTG+CT (p<0.01). Score on the MLHFQ demonstrated a significant decrease both in SIMTG+CT (p=0.0002) and in IMTG+CT (p<0.0001). In comparison between groups, a significant reduction favoring IMTG+CT was found (p<0.01). There was a significant increase of MIP in SIMTG+CT (p=0.0126) and in IMTG+CT (p<0.0001). A significant increase in IMTG+CT was observed when compared to SIMTG+CT (p<0.001). The FRAP demonstrated a significant increase both in SIMTG+CT (p=0.0016) and in IMTG+CT (p<0.0001). Between groups, a significant increase was observed favoring IMTG+CT (p=0.0069). The hsCRP demonstrated a significant decrease in SIMTG+CT (p=0.0589) and in IMTG+CT (p<0.0056). There was no significant difference between groups (p=0.3916). There was a significant intragroup increase of MEP in SIMTG+CT (p=0.0106) and in IMTG+CT (p=0.0252), and of NOx in SIMTG+CT (p=0.0015) and in IMTG+CT (p=0.0150). The IMTG+CT had significant increases in FVC (p=0.0070), in FEV1 (p=0.0022), in SMIP (p<0.0001) and in Tlim (p=0.0046). The AOPP did not present significant differences between groups. This study demonstrated for the first time that high-intensity short-length IMT can enhance the effects of CT on FC, inspiratory muscle strength, QoL and antioxidant profile. Moreover, it improved inspiratory muscle resistance and pulmonary function in post- CABG patients in the Phase II of CR. Such findings are clinically relevant in demonstrating that IMT can be a low cost and easy to insert complement to RC programs.